The influence of implementation work-based learning model on learning innovation skills student’s - Negara, Irma Manda; Hidayati, Nurul (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This study aimed to analyze the influence of internship as a form of the WBL model to LIS students, in terms of the assessment theory of work-based learning and framework of 21st-century skills. The method used is descriptive quantitative, with respondents students who have done internships. The results showed that there are significant WBL (X) on critical thinking and problem-solving skills (Y1), indicated by the results of the significance value 0.000 ttable 2.024. Next, there is the influence of WBL (X) on communication skills (Y2), seen from the significance value of 0.000 ttable 2,024. There is the influence of WBL (X) on collaboration skills (Y3), seen at a significance value of 0.000 ttable 2,024. There is no significant and positive relationship between the implementation of WBL and students' Creativity and Innovation skills (Y4). This can be seen when the linearity test is carried out. The implementation of an internship can contribute to the development of skills covered in LIS, except for creativity and innovation skills.